"There's no billing code for empathy" - Animated comics remind medical students of empathy: a qualitative study. Issue 1 (December 2016) - Tsao, Pamela; Yu, Catherine
Abstract Background Physician empathy is associated with improved diabetes outcomes. However, empathy declines throughout medical school training. This study seeks to describe how comics on diabetes affect learning processes for empathy in medical students. Methods All first- or second-year students at a Canadian medical school were invited to provide written reflections on two comics regarding diabetes and participate in a focus group. Responses were analyzed qualitatively for emergent themes. Students completed the Jefferson Scale of Physician Empathy (JSPE) at baseline, after the comic, and after the focus group. Linear mixed model statistical analyses were performed. Results Thirteen first-year and 12 second-year students participated. Qualitative analysis revealed four themes: 1) Empathy decline and its barriers; 2) Impact of the comic and focus group on knowledge, attitudes and skills; 3) Role of the comic in the curriculum as a reminder tool of the importance of empathy; 4) Comics as an effective medium. Baseline mean JSPE scores were 116.4 (SD 10.5) and trended up to 117.2 (SD 12.5) and 119.6 (SD 15.2) after viewing the comics and participating in the focus groups, respectively (p  = 0.08). Conclusions Animated comics on diabetes are novel methods of reminding students about empathy by highlighting the patient perspective.